The influence of climate on species distribution over time and space during the late Quaternary. (1st October 2016) - Carotenuto, F.; Di Febbraro, M.; Melchionna, M.; Castiglione, S.; Saggese, F.; Serio, C.; Mondanaro, A.; Passaro, F.; Loy, A.; Raia, P.
Abstract: Understanding the effect of climate on the composition of communities and its change over time and space is one of the major aims in ecology and paleoecology. Herein, we tackled on this issue by studying late Quaternary large mammal paleocommunities of Eurasia. The late Quaternary was a period of strong environmental instability, especially characterized by the occurrence of the last glacial maximum (LGM). We used community phylogenetics and joint species distribution models in order to understand the factors determining paleocommunity composition in the late Quaternary. Our results support the existence of strong climatic selection operating on the LGM fauna, both through the disappearance of warm-adapted species such as Elephas antiquus, Hippopothamus amphibious, and Stephanorhinus hemitoechus, and by setting the stage for the existence of a community characterized by cold-adapted large mammals. Patterns of abundance in the fossil record, co-occurrence between species pairs, and the extent of climatic forcing on faunal composition, differ between paleocommunities, but not between extinct and extant species, which is consistent with the idea that climate change, rather than the presence of humans, exerted a major effect on the survival of the late Quaternary megafauna. Highlights: We studied the influence of climate on composition and turnover of large mammal communities at the end of the Quaternary. We found strong evidence that climatic control was highest during the Last Glacial Maximum. Early Holocene ecosystems were reduced in both diversity and functioning.